Assessment of peritoneal thickness using CT in relation to dialysis adequacy in peritoneal dialysis patients. Issue 6 (23rd August 2021) - Barutcu Atas, Dilek; Demircioglu, Ozlem; Cimsit, Canan; Velioglu, Arzu; Arikan, Hakki; Asicioglu, Ebru
Abstract: Studies assessing peritoneal thickness by CT in peritoneal dialysis (PD) patients are lacking. In this study, we aimed to investigate the association between peritoneal thickness as measured by CT and dialysis adequacy with peritoneal membrane characteristics in PD patients. Ninety‐four PD patients were enrolled. Peritoneal thickness was measured by CT. Patients with and without a decrease in Kt/V of at least 0.3 over time were classified as Group 1 and Group 2, respectively. An increase of 0.1 unit of dialysate/plasma (D/P) creatinine over time were considered significant. The relationship between peritoneal membrane thickness, change in Kt/V, and peritoneal membrane characteristics were investigated. There were 31 (33.0%) patients in Group 1. The duration of PD (86.0 ± 64.1 vs. 59.6 ± 45.2 months, p : 0.023), peritoneal thickness (1.02 ± 0.37 vs. 0.87 ± 0.21 mm, p : 0.015), peritoneal calcification (7 [22.6%] vs. 3 [4.8%] patients, p : 0.013], increased D/P creatinine ratio (14 [45.2%] vs. 14 [22.2%] patients, p : 0.031) and CRP (13.9 ± 11.2 vs. 7.1 ± 4.8 mg/L, p : 0.045) were significantly higher in Group 1, whereas albumin (3.6 ± 0.5 vs. 3.8 ± 0.6 g/dL, p : 0.047) and parathyroid hormone (355.2 ± 260.2 vs. 532.1 ± 332.9 ng/L, p : 0.015) levels were significantly lower. Peritoneal thickness was significantly correlated with duration of PD ( r : 0.775, p < 0.001) and CRP ( r : 0.282, p : 0.006). Regression analysis showed that peritoneal thickness (Exp ( B ) [95% CI]: 0.029 [0.003–0.253], p : 0.001) was independent predictor of decreased Kt/V in PD patients. In conclusion, prolonged PD duration and increased peritoneal thickness are associated with a decrease in Kt/V over time. CT may be an alternative and noninvasive method instead of peritoneal biopsy for determining the structural changes of the peritoneal membrane .